Analysis of Market System Mapping Patterns and Potential for Milkfish Cultivation in Pangkahwetan Village - Nurman Setiawan Fadjar; Risqi Noor Hidayati Putri (International Journal of Applied Business and International Management, 2024)
One of the common species for aquaculture in Indonesia is milkfish (Chanos chanos). Pangkah Wetan Village in Gresik Regency is one of the areas that have the potential or value for milkfish aquaculture, which is influenced by the majority of the population who have a livelihood in the fisheries sector and milkfish is relatively easy to cultivate due to its fast growth. This research examines the potential of milkfish, the milkfish market system, and the strategy for developing milkfish cultivation through an analysis of the market system approach. The analysis is carried out to identify the various barriers that exist in the market system and to place the focus on how to overcome these obstacles. It was discovered that the cause of the low productivity of milkfish aquaculture was due to limitations in supporting services, not in the actors. The basic causes of this productivity include various seedlings' quality, limited artificial feed, low utilization of technology, low access to capital, low marketing levels, and the minimal role of related institutions. Hence, systemic intervention is necessary in terms of support services in order to improve the welfare of the community which in turn will increase the income of farmers.